External Morphology and Distinguishing Characters of Male and Female Pupae of Ailanthus Webworm, Atteva fabriciella Swed. (Lepidoptfra : Yponomeutidae - Singh, Pratap; Sharma, Krishan Kanta (Indian Forester, 1979)
External morphology of pupae of A.fabriciella and tHe distinguishing characters of male and female are given. A comparison of pupae of A.fabriciella and A. aurea is also made.